Predictors of depression: lifestyle choices during the pandemic - Tesarova, Sarka; Pekacek, Ondrej; Porrovecchio, Alessandro (Frontiers in Psychology, 2023)
Our study intends to specify the impact of the singular pandemic stressors on the population and also quantify the contribution of different predictors of depression; some of them are stronger than the others, and this research shows how the whole effect is divided into single items. This research also includes an analysis of how behavioral patterns appear in different groups of the population and how they mark the psychological well-being of these groups with regards to various factors. We mainly targeted social media's role and analyzed the impact of its consumption on symptoms of depression in different groups divided by age and other characteristics.